Mao. 22 - Takahashi, Rumiko, 1957-; Roman, Annette (Shōnen Sandē komikkusu., 2025)
"Nanoka encounters an ayakashi on her own and attempts to single-handedly exorcise it and save its host. But when she receives help from an unexpected source, her jealousy is triggered. Will dense Mao understand why? Then, yet more is revealed about the tangled truth behind Sana's death..."--